Manajemen Proyek Otomasi Industri pada Sistem Lampu Otomatis di Area Gudang Pabrik Manufaktur - Ahmad Prasetyo; Meutia Dwina Khairunisa; Seli Aprilia (Program Studi Teknik Industri Universitas Teknologi Sumbawa, 2026)
This study discusses the application of industrial automation project management to an automatic lighting system in a manufacturing warehouse. The research background stems from low energy efficiency caused by uncontrolled manual lighting systems where lights are frequently left on unnecessarily. This study aims to comprehensively analyze the implementation of project planning, budgeting, risk management, execution, and evaluation for automation projects. The methodology employs a descriptive case study with a conceptual analysis approach based on the modern project management framework (PMBOK). The designed system utilizes Passive Infrared (PIR) and Light Dependent Resistor (LDR) sensors as inputs, a microcontroller as the processor, and LED lights as output. Results show that the automatic lighting system provides 30–60% energy savings potential, improves workplace safety, and reduces dependence on manual operations. Risk management analysis identified six key risks with structured mitigation strategies. KPI-based evaluation covers energy saving rates, system reliability, operational cost reduction, and occupational safety performance. Development recommendations include IoT integration for real-time monitoring and system scalability to other areas. This research confirms that automation project success is determined not only by technical aspects but is significantly influenced by structured project management quality.